Menghindari Dampak Sistemik dengan Pemenuhan Net Stable Funding Ratio Bank CIMB Niaga - Zuhri, Muhammad; Lamhot; Girsang , Tonggo Sangap Timbul (Cattleya Darmaya Fortuna, 2024)
The experience of the global financial crisis that occurred in 2008 shows that even though the Bank's capitalization is adequate, if the Bank does not manage its liquidity carefully, it can disrupt the Bank's business continuity. The difficulties faced by most banks at that time were caused by their inability to meet the standards related to the basic principles of measuring and implementing liquidity risk management. This caused the Bank to be exposed to systemic impacts when the Bank failed to take into account the impact arising from a large funding gap. High interconnectedness between financial systems tends to exacerbate the systemic impact.